1998
DOI: 10.1523/jneurosci.18-09-03433.1998
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Response to Changing Neuronal Input in the Lobster(Panulirus Interruptus)Stomatogastric System: Slow Muscle Properties Can Transform Rhythmic Input into Tonic Output

Abstract: Slow, non-twitch muscles are widespread in lower vertebrates and invertebrates and are often assumed to be primarily involved in posture or slow motor patterns. However, in several preparations, including some well known invertebrate "model" preparations, slow muscles are driven by rapid, rhythmic inputs. The response of slow muscles to such inputs is little understood. We are investigating this issue with a slow stomatogastric muscle (cpv1b) driven by a relatively rapid, rhythmic neural pattern. A simple mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 27 publications
(29 reference statements)
1
41
0
Order By: Relevance
“…This contrasts with the effects of A-ASTs, which have been shown to modulate muscle contraction both pre-and postsynaptically (Jorge-Rivera and Marder, 1997;Kreissl et al, 1999). Although there were no direct effects of C-AST on muscle contraction, we found that C-AST's ability to decrease contraction amplitude was in fact due to an indirect effect at the neuromuscular junction; namely, a decrease in facilitation resulting from the decreased cycle frequency, as has been seen in other studies of this system (Mahadevan et al, 2004) as well as other crustacean neuromuscular systems (Jorge-Rivera et al, 1998;Mercier and Wilkins, 1984;Morris and Hooper, 1998). Interestingly, because C-AST consistently decreased cycle frequency in all lobsters, a decrease in facilitation was certainly also present in the preparations in which contraction amplitude increased.…”
Section: Discussionsupporting
confidence: 68%
“…This contrasts with the effects of A-ASTs, which have been shown to modulate muscle contraction both pre-and postsynaptically (Jorge-Rivera and Marder, 1997;Kreissl et al, 1999). Although there were no direct effects of C-AST on muscle contraction, we found that C-AST's ability to decrease contraction amplitude was in fact due to an indirect effect at the neuromuscular junction; namely, a decrease in facilitation resulting from the decreased cycle frequency, as has been seen in other studies of this system (Mahadevan et al, 2004) as well as other crustacean neuromuscular systems (Jorge-Rivera et al, 1998;Mercier and Wilkins, 1984;Morris and Hooper, 1998). Interestingly, because C-AST consistently decreased cycle frequency in all lobsters, a decrease in facilitation was certainly also present in the preparations in which contraction amplitude increased.…”
Section: Discussionsupporting
confidence: 68%
“…The consequences of motor neuron activity therefore cannot be understood without understanding this transformation (see Chiel and Beer, 1997, for a full discussion of this issue). Work on the pyloric muscles of the lobster stomatogastric system well demonstrates this issue (Morris and Hooper, 1998;Morris et al, 2000;Thuma et al, 2003). Pyloric motor neurons fire bursts of action potentials approximately once per second.…”
Section: Introductionmentioning
confidence: 90%
“…Synaptic integration has been studied extensively in crustaceans, particularly at the neuromuscular junction (Atwood, 1976;Atwood and Wojtowicz, 1986;Bittner, 1968;Bykhovskaia et al, 2004;Dudel and Kuffler, 1961;JorgeRivera and Marder, 1997;Jorge-Rivera et al, 1998;Katz et al, 1993;Morris and Hooper, 1997;Morris and Hooper, 1998;Morris and Hooper, 2001;Msghina et al, 1998). STG motor neurons provide the large gastric mill muscle fibers with a number of spatially separated synaptic sites, which ensures that the entire muscle fiber receives depolarizing inputs and contracts as a whole.…”
Section: Consequences For Behaviormentioning
confidence: 99%